The Combined Strengthening Effect of CFRP Wrapping and NSM CFRP Laminates on the Flexural Behavior of Post-Tensioning Concrete Girders Subjected to Partially Strand Damage - Daraj, A. J.; Al-Zuhairi, A. H. (Engineering, Technology & Applied Science Research, 2022)
The studies on unbonded post-tensioned concrete members strengthened with Carbon Fiber Reinforced Polymers (CFRPs) are limited and the effect of strengthening on the strain of unbonded pre-stressed steel is not well characterized. Estimating the flexural capacity of unbound post-tensioned members using the design methodology specified in the design guidelines for FRP strengthening techniques of bonded post-tensioned members does not provide a reliable evaluation. This study investigates the behavior of unbonded post-tensioned concrete members with partial strand damage (14.3% and 28.6% damage) and strengthened with CFRP laminates using a near-surface mounted technique with and without U-wrap anchorages. The experimental results showed that the use of CFRP laminates significantly affects strand strain, especially with the use of anchors. The CFRP reinforcement affected flexural strength, crack width, and midspan deflection. However, the flexural stiffness of strengthened members during the serviceability phases is critical as strand damage ratios increase. In comparison with the nondamaged girder, the NSM-CFRP laminates enhanced the flexural capacity by 11% and 7.7% corresponding to strand damage of 14.3% and 28.6% respectively. Additionally, semiempirical equations were proposed to predict the actual strain of unbonded strands whilst considering the effects of FRP laminates. The suggested equations are simple to apply and provide accurate predictions with little variance.